Finite element analysis on the effect of workpiece geometry on the quenching of ST50 steel - Hamouda, A.M.S.; Sulaiman, S.; Lau, C.K. (Elsevier, 2001)
The finite element method (FEM) is employed to investigate the residual stress state and the variation of internal stresses in ST50 steel quenched from 600 to 0°C. Three different geometrical shapes of model were used, namely cylinder, cone and pyramid-shaped cone. Thermal analysis is first performed to obtain the cooling curves for the core and surface of the models, and this is followed by a full structural analysis. The results of the cylinder bar obtained from the computer simulation are compared with those experimentally determined values that are available in the literature and there appears to be a good measure of agreement. The study found that at the initial stages of the quenching process, the residual stresses were tensile at the surface and compressive in the core, however, towards the end of the quenching process, the tensile residual stresses switched to the core and compressive residual stresses at the surface. Under the same quenching conditions, if the models with different geometrical shape were tested, it has been found that the geometry has significant effect on the distribution and the magnitudes of the residual stress. Although the cylinder and the cone were different in shapes, but the residual stress state were not much in difference. Only when the cone turn into pyramid-shaped cone, the results were different and higher values of internal residual stress.